Making a Video as an Alternative Task to Improve the Students’ Motivation to Practice Speaking English: The Case at Grade VII B of SMP N 1 Ungaran - Ruchajat, Listiani (Universitas Negeri Semarang, 2018)
This research investigates making a video, as an alternative task to improve the students’ motivation to practice speaking English. The case at grade VIIB of SMP N 1 Ungaran.The objectives of this research are to describe how video making task can improve the students’ motivation to practice speaking English, to describe how video making task is implemented to improve the students’ motivation to practice speaking English, and to describe why video making task can be implemented to improve the students’ motivation to practice speaking English.This is a kind of classroom action research which belongs to descriptive qualitative research. The source of data are the results of students’ responds toward questionnaire given at the end of three cycles conducted by the researcher, supported by the results of students’ interview and students’ tasks.The findings of the research are: most of students liked to do the task since it can make them happy and fun, also be able to improve their confidence and speaking competence. The task also made the students to have motivation to practice speaking English without teacher’s order and outside English class. The task also helps to improve the students’ understanding toward the lesson materials and speaking competence.Based on the findings, the researcher suggests the other teachers to apply video making task in their class to improve their students’ motivation to practice speaking English using an appropriate topic.